Systematics and evolution of small genera of carnivorous plants - Cross, Adam; Paniw, M.; Scatigna, A.; Kalfas, N.; Anderson, B.; Givnish, T.; Fleischmann, A. (2018)
Carnivory is found in eight additional plant families besides the well-studied and speciose Droseraceae, Lentibulariaceae, Nepenthaceae, and Sarraceniaceae. These include six species-poor or monogeneric families (Drosophyllaceae, Dioncophyllaceae, Cephalotaceae, Roridulaceae, Byblidaceae); the carnivorous genus Philcoxia in the otherwise noncarnivorous, species-rich Plantaginaceae; and at least one species in each of three monocot genera in which carnivory is not a universal trait: Bromeliaceae (Brocchinia and Catopsis) and Eriocaulaceae (Paepalanthus). We review the current knowledge of these nine genera with a focus on their biology, ecology, and evolution. Although the small carnivorous genera are not diverse in terms of species number, they contain some of the most unique, peculiar, and ecologically novel carnivorous plants. The species include plants reliant upon digestive mutualism with insects; a carnivorous epiphyte; and a part-time carnivore.